GRAMMATICAL ERRORS MADE BY THE SEVENTH GRADE STUDENTS IN TELLING DAILY ACTIVITIES OF SMP PGRI 1 PALEMBANG - Ferri Hidayad (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThe main problem of this study was “What grammatical errors are made by the seventh grade in telling their daily activities at SMP PGRI 1 Palembang?” Therefore, the main purpose students of this study was to find out the errors made by the seventh grade students in telling daily activities of SMP PGRI 1 Palembang. The descriptive method was applied in this study. The population of this study was all the seventh grade students of SMP PGRI 1 Palembang in the academic year of 2009/2010 with the total number of the students as the population was 173 students and the sample students consisted of 20 assigned by using cluster random sampling. It consisted of 10 items in the telling daily activities. The result of the test were analyzed by means of percentage calculation. Based on the research, it was found out that the seventh grade the students of SMP PGRI 1 Palembang made errors in telling daily activities in subjects and verbs (10%), verb agreement, tense, and form (9.6%), full subordination (10%), the verbal's (10.4%), pronoun form, agreement, and reference (10%), word form (10%), word order (10%), parallel structure (10%), unnecessary repetition (10%), and correct usage (10%). In short, the seventh grade students of SMP PGRI 1 Palembang still made ten kinds of the grammatical errors in telling their daily activities.Keywords: Grammatical Errors, Daily Activities